A Comparative Study of the Quality of Higher Education Provision in Public and Private Universities in Bangladesh - Amin, Md. Ruhul; Sheikh, Md. Rashidul Islam (Global Journal of Educational Studies, 2024)
The evolution of a modern society largely depends on the essence of quality higher education. In a developing country, higher education has enormous potential to foster its development. Universities all over the world are changing actors of culture and remain the center of transformation and growth. Different Education Commissions have been formed in Bangladesh to explore the potentialities and create highly skilled human resources to contribute the national development (Topader, 2021). Due to the economic and globalization change emphasis on the quality education in education policy across the world. As a result, policymakers, academicians, and professionals in Bangladesh have expressed various issues regarding the quality of higher education. Over the last two decades, the standard of higher education in Bangladesh has steadily deteriorated (Rabbani & Chowdhury, 2014). In this regard, the government, ministry, and UGC have taken various initiatives to ensure quality higher education, especially at the tertiary level, to meet global demand. In this regard, this research aims to learn more about a particular scenario of higher education quality and investigate policy options for higher education in Bangladesh. In this connection, this study tried to determine the specific design of quality higher education and analyze the policy options for higher education in Bangladesh.